PENGARUH FAKTOR EKONOMI, SOSIAL DAN DEMOGRAFI TERHADAP PENGIRIMAN REMITAN MIGRAN WARGA DESA PANDAK GEDE YANG BERMUKIM DI KABUPATEN JEMBRANA - Adisavitri, Anan Agung; Sudibia, I Ketut; Marhaeni, AAIN (PIRAMIDA; Vol 12 No 1 (2016), 2016)
The choice of population to move based on the multiple motives, where the primary motive of people to move is due to economic motives. Population mobility is the one srategy to accelerate equitable development by their home area both money and goods, which in migration theory known as remittances. The remittances that were sent to the area the origin indicate the tightly of kindship ties of the people who migrate with the area of origin. This study aims to determine: 1) the average proportion of remittances sent to the region of origin by migrants working in agriculture and non-agricultural; 2) the average difference of remittances sent by migrants working in agriculture and non-agricultural; 3) the effect of education, work experience, employment and the age of the revenue; 4) the effect of education, work experience, employment, age, and income on remittances; 5) analyze the role of income in mediating the effects of education, work experience, employment and the age of the remittances. The study was conducted in Jembrana with sampling method is stratified random sampling. Migrants are being sampled is permanent migrants Pandak Gede village residents who live in Jembrana. The total sample of 92 respondents. Data were analyzed using descriptive analysis, comparative analysis and analysis of associative form of path analysis and Sobel test. The results showed that the minimum proportion of remittances sent by 0,39 percent and the maximum proportion of remittances by 8.19 percent with an average of 2.75 percent from income. There are significant differences of remittances sent by migrants working in agriculture and non-agriculture. Education, work experience, employment and age positive and significant impact on revenues. Education, work experience, employment, age and income positive and significant impact on the remittances sent. In addition, revenue is mediating variables in the influence of education, work experience, employment and the age of the remittances sent to their home area.
Keywords: Permanent Migrant, Remittance, Income